2014
DOI: 10.3390/biology3040670
|View full text |Cite
|
Sign up to set email alerts
|

DNA Modifications: Function and Applications in Normal and Disease States

Abstract: Epigenetics refers to a variety of processes that have heritable effects on gene expression programs without changes in DNA sequence. Key players in epigenetic control are chemical modifications to DNA, histone, and non-histone chromosomal proteins, which establish a complex regulatory network that controls genome function. Methylation of DNA at the fifth position of cytosine in CpG dinucleotides (5-methylcytosine, 5mC), which is carried out by DNA methyltransferases, is commonly associated with gene silencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(101 citation statements)
references
References 281 publications
(394 reference statements)
0
99
0
2
Order By: Relevance
“…27 De novo metiltransferazlar adı verilen DNMT3a, DNMT3b ve DNMT3L embriyonik kök hücrelerinde yüksek derecede ifade edilir, imprinting işleminde DNA metilasyonundan sorumludur. [28,29] DNA metilasyonu gelişim ve farklılaşma, genomik imprinting, X kromozomunun inaktivasyonu, genomu transpozonlardan koruma gibi farklı biyolojik fonksiyonlara aracılık etmektedir. 19,28,30 DNA metilasyon düzeyinin yaşlanmaya bağlı olarak değişimi çeşitli çalışmalarda gösterilmiştir.…”
Section: Dna Meti̇lasyon Deği̇şi̇mleri̇ Ve Yaşlanmaunclassified
See 1 more Smart Citation
“…27 De novo metiltransferazlar adı verilen DNMT3a, DNMT3b ve DNMT3L embriyonik kök hücrelerinde yüksek derecede ifade edilir, imprinting işleminde DNA metilasyonundan sorumludur. [28,29] DNA metilasyonu gelişim ve farklılaşma, genomik imprinting, X kromozomunun inaktivasyonu, genomu transpozonlardan koruma gibi farklı biyolojik fonksiyonlara aracılık etmektedir. 19,28,30 DNA metilasyon düzeyinin yaşlanmaya bağlı olarak değişimi çeşitli çalışmalarda gösterilmiştir.…”
Section: Dna Meti̇lasyon Deği̇şi̇mleri̇ Ve Yaşlanmaunclassified
“…[28,29] DNA metilasyonu gelişim ve farklılaşma, genomik imprinting, X kromozomunun inaktivasyonu, genomu transpozonlardan koruma gibi farklı biyolojik fonksiyonlara aracılık etmektedir. 19,28,30 DNA metilasyon düzeyinin yaşlanmaya bağlı olarak değişimi çeşitli çalışmalarda gösterilmiştir. Yaşlanma ve DNA metilasyonu arasındaki ilişki ilk kez somon balığında yapılan çalışmalarda öne sü-rülmüştür.…”
Section: Dna Meti̇lasyon Deği̇şi̇mleri̇ Ve Yaşlanmaunclassified
“…Correct methylation occurrence is necessary for the suitable binding of MBPs. Different roles of MBPs can be seen in different types of cancers 17 . Alternative splicing and their role in cancer is also getting more interest, as both changes in splicing factor expression and cis-mutations can cause disease.…”
Section: Some Other Diseasementioning
confidence: 99%
“…It was determined that DNA methylation effect several genes by misregulating, which could lead to cardiovascular diseases. Also; loss of function of DNA methyltransferases cause to increased resistance to brain damaged by ischemia and together, it was shown that; there is a possible link between DNA methylation and cerebral ischemia 17 .…”
Section: Cardiovascular Diseases and Cerebral Ischemiamentioning
confidence: 99%
“…Genome-wide association studies have identified that some CDKN2A or CDKN2B genetic variants are susceptible to CHD (8)(9)(10). As recently reported, many human diseases, including cardiovascular disease, could be influenced by aberrant DNA methylation modification (11). Aberrant methylation of cytosine-phosphate-guanine (CpG) islands in gene promoters is associated with transcription silencing and activity (3).…”
Section: Introductionmentioning
confidence: 99%